2022
DOI: 10.5897/ajfs2022.2175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus aurantifolia juice on bodyweight and haematological indices of wistar rats

Abstract: Citrus aurantifolia (Lime) is a citrus fruit and an excellent source of vitamin C and flavonoids which have unique antioxidant properties. This study determined the effects of C. aurantifolia on the bodyweight and hematological indices of rats. A total of 20 rats of both sex weighing between 120 and 130 g were randomized into 4 groups of five rats each and used. Group A: Normal Control; Group B: 2 ml/kg of C. aurantifolia fruit juice; Group C: 4 ml/kg of C. aurantifolia fruit juice; Group D: 8 ml/kg of C. aura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This increase in creatinine levels could be associated with increased survivability possibly due to better nutritional status and muscle mass which is in line with the research carried out by Storm et al [19] and Fink et al [24]. Medicinal plants improve the biochemical profiles of experimental animals immensely which could be because of its phytochemical, mineral or vitamin composition as revealed in previous studies [25][26][27]. Urea is a major nitrogenous waste product of metabolism that is generated from protein breakdown thus an increase in dietary protein results in increased urea production [28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This increase in creatinine levels could be associated with increased survivability possibly due to better nutritional status and muscle mass which is in line with the research carried out by Storm et al [19] and Fink et al [24]. Medicinal plants improve the biochemical profiles of experimental animals immensely which could be because of its phytochemical, mineral or vitamin composition as revealed in previous studies [25][26][27]. Urea is a major nitrogenous waste product of metabolism that is generated from protein breakdown thus an increase in dietary protein results in increased urea production [28].…”
Section: Discussionsupporting
confidence: 82%
“…However, the increase in ALT and ALP level could either be a sign of an underlying condition affecting the liver or could be due to increase in muscular activity of the rats due to availability of more energy and protein in their diet. Although this study revealed increased kidney and liver function parameters, our earlier studies showed that processed breadfruit does not have adverse effect on the lipid profile, random blood glucose concentration, malondialdehyde level and lactate dehydrogenase activity of Wistar rats [31,32].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, C. aurantifolia has a proven therapeutic effect on leukopenia patients. Research from Ezeigwe et al, (2022) [122] also mentioned that C. aurantifolia juice, apart from functioning as an immune booster, can also function in weight management.…”
Section: Leukopeniamentioning
confidence: 99%
“…Currently, hepatic diseases are becoming a major concern to health practitioners across the globe as mortality and morbidity are on the rise daily. Several studies have reported their beneficial properties in the management of various ailments, especially diabetes [2,3]. "Considerable evidences showed that indigenous medicinal plants in Nigeria form an important component of the natural wealth of the country" [4].…”
Section: Introductionmentioning
confidence: 99%
“…"Diabetes mellitus (DM) is a chronic disorder affecting carbohydrate metabolism and involving hyperglycemia, as a result of deficiencies in insulin release, action, or even both" [2]. These range from defects that lead to resistance to insulin action to autoimmune destruction of the pancreatic B-cells with subsequent insulin shortage ; and have since been categorized into Type I and Type II.DM, when not properly managed, can lead to a series of complications and consequently to injuries in various tissues and poor quality of life" [5,6].…”
Section: Introductionmentioning
confidence: 99%